Evaluation of the Willems and Cameriere’s dental age estimation methods in Turkish children–A modified version of Cameriere’s method - Hatice Cansu Kış; Cansu Görürgöz; Merve Başol; Emin Murat Canger; Bengi Öztaş (Forensic Science International: Reports, 2020)
The purpose of this study was to compare the accuracy of dental age estimation results obtained using the Willems and Cameriere methods in a large Turkish sample. A further aim was to adapt Cameriere’s regression equation to the Turkish population and to produce an updated regression model appropriate for Turkish children. Finally, we compare the results of the Cameriere and Willems methods.The study group was obtained from two dental radiology department archives. The total sample consisted of 1878 Turkish children (972 boys, 906 girls) aged between five and 15 years. Willems and Cameriere’s age estimation methods were applied. Cameriere’s method performed almost identically for both sex groups. However, the Willems method performed differently for boys and girls within the age range of 8–14. While the Willems method overestimated the dental age than the chronological age in all age groups, Cameriere's method underestimated the dental age than the chronological age in the 8–14 age group.Both Cameriere’s and Willems methods are applicable to the Turkish population. However, researchers should consider that the Cameriere method unbiasedly estimates an individual's age depending on chronological age, while the Willems method overestimates this in all age groups.